Equity, Vulnerability and Resilience in Social-Ecological Systems: a contemporary example from the Russian Arctic - Forbes, Bruce C. (2008)
Environmental and social problems are tightly linked in coupled social-ecological systems in the Arctic. The article discusses the importance of equity as a factor in the adaptive capacity of a region undergoing relatively rapid climate change and simultaneous land use change in the northwest Russian Arctic.